Integrasi Sistem Informasi Manajemen Pendidikan Dengan Aplikasi Akademik Mobile Pada Sekolah Menengah PertamaYPI Cempaka Putih Bintaro - Atiqah Meutia Hilda; Tuti Awaliyah; Arry Avorizano; Arien Bianingrum Rossianiz; Lutfan Zulwaqar (Prosiding Seminar Nasional Teknoka, 2022)
The Education Management Information System (MIS) has 3 important applications, including the General Education Information System, the Main Education Information System and the Education Support Information System. Where the General Information System is built school Web Portal as a school identity in a global world. The purpose of this research is to assist schools in implementing Educational Management Information Systems (MIS) that are mutually integrated in data processing, decision making and improving the quality of information services. This system was built using the Laravel PHP framework version 5.6.16 supported by a MySQL database to process the database. The existence of Education Management Information System Integration (MIS) built both on the web and mobile-based shows that the world of education can be even better in the use of information technology. The test results show a percentage of 81.89%, which means that the results of the system assessment can be categorized as very very good to be accessible by employees, teachers, students and the community which is the identity of schools in the global world so that the wider community can get to know the school more easily.